Construction of Husband and Wife Worker Relationship Patterns Based on the Concept of Gender Equality - Syarif Hidayatullah; Nerisma Eka Putri (STKIP Taman Siswa Bima, 2025)
This study examines the construction of husband-wife relationship patterns based on gender equality concepts, particularly in dual-career families. Traditional family structures have historically placed men in public domains while confining women to domestic responsibilities, creating gender inequality reinforced by patriarchal culture. This library research employs a descriptive-analytic approach to explore how the